Service Development and Implementation - A Review of the State of the Art - Torney, M.; Kuntzky, K.; Herrmann, C. (Cranfield University Press, 2009)
As service development is a complex and interdisciplinary issue, service research has been conducted in numerous disciplines and sectors. As a result, different approaches containing manifold models, methods, and tools with different foci have been developed and discussed in recent years. Due to the diverse nature of the approaches, it is a challenge for organizations to distinguish between them. Against this background, the aim of this paper is to propose a framework for classification and, based on the framework, to present an overview of the state of the art in the research field of service development and implementation.
Organised by: Cranfield University
Keywords: Service Development and Implementation; Service Engineering; State of the Art